Should we protect extirpated fish spawning aggregation sites?. (January 2020) - Chollett, Iliana; Priest, Mark; Fulton, Stuart; Heyman, William D
Abstract: Some locations have extraordinary ecological and conservation significance and subsequently need protection to guarantee the persistence of species that depend on them. Fish Spawning Aggregation (FSA) sites, where fish congregate to breed, are examples of such places, but are being extirpated worldwide through overfishing. Although transient FSA sites figure prominently as priority areas for conservation, extirpated aggregations, that due to current low abundance at spawning times are no longer recognizable as FSAs, represent a dilemma for managers. Given the limited resources available for conservation actions, should we protect extirpated FSAs or omit them from spatial management plans? Here we present two contrasting points of view, look into the mechanisms associated with the emergence and maintenance of aggregation sites, and review available evidence of recovery in the field. Of the 53 extirpated FSA sites examined, 9 (17%) reported recovery, always after strict management was implemented. All recovered sites were located in the wider Caribbean and western Atlantic. We make the case that extirpated FSAs seem to have the potential to recover and their protection may provide a cost effective way to help rebuild fisheries. It is unclear, however, if a remnant population is needed to allow recovery. Current methods used to monitor and assess FSA status and extirpation are not consistent, hindering site trend analysis, between-site comparisons and meta-analysis. We suggest that monitoring and management should be made more consistent and strengthened to boost FSA recovery. Highlights: Fish spawning aggregations (FSAs) are disappearing through overfishing. It is currently unclear if there is value in protecting extirpated FSAS. We supplement the best database on FSAs available. Recovery of FSAs is possible in areas with effective management.